Physical Activity and Hip Fracture Disability: A Review - Ray Marks (Journal of Aging Research)
Objective. The present paper examines pertinent literature sources published in the peer-reviewed English language between 1980 and November 1, 2010 concerning hip fractures. The aim was to highlight potential intervention points to offset the risk of incurring a hip fracture and its attendant disability. Methods. An in-depth search of the literature using the key terms: disability, epidemiology, hip fracture, prevention, and risk factors was conducted, along with data from the author's research base detailing the disability associated with selected hip fracture cases. All articles that dealt with these key topics were reviewed, and relevant data were tabulated and analyzed. Results. Hip fractures remain an important but potentially preventable public health problem. Among the many related remediable risk factors, low physical activity levels are especially important. Related determinants of suboptimal neuromuscular function also contribute significantly to hip fracture disability. Conclusion. Physical activity participation can help to reduce the prevalence and excess disability of hip fractures and should be encouraged.